2011
DOI: 10.1111/j.1468-3083.2010.03789.x
|View full text |Cite
|
Sign up to set email alerts
|

Balancing efficacy and safety in the management of atopic dermatitis: the role of methylprednisolone aceponate

Abstract: Although emollients can be sufficient to manage mild atopic dermatitis (AD), acute flares resulting in moderate-to-severe symptoms require treatment with anti-inflammatory agents, such as topical corticosteroids (TCs) and topical calcineurin inhibitors (TCIs). This review examines the role of a member of the newest class of TCs, the fourth-generation compound methylprednisolone aceponate (MPA) in AD management, with reference to the chemical structure, pharmacokinetics, efficacy in AD, safety assessed in precl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
16

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 43 publications
0
25
0
16
Order By: Relevance
“…Methylprednisolone aceponate is included in the group of potent TCS (category III/IV); triamcinolone acetonide and bethametasone valerate are reference TCS also included in this group . Multiple double‐blind studies, both placebo‐controlled and compared to reference TCS, have shown a high clinical efficacy of MPA in the treatment of eczema after 1–4 weeks of application once daily .…”
Section: Efficacy Of Mpamentioning
confidence: 99%
See 1 more Smart Citation
“…Methylprednisolone aceponate is included in the group of potent TCS (category III/IV); triamcinolone acetonide and bethametasone valerate are reference TCS also included in this group . Multiple double‐blind studies, both placebo‐controlled and compared to reference TCS, have shown a high clinical efficacy of MPA in the treatment of eczema after 1–4 weeks of application once daily .…”
Section: Efficacy Of Mpamentioning
confidence: 99%
“…Epidermal thinning is partly reversible, but atrophy of the dermis and even subcutaneous tissue is often permanent. Striae and telangiectasias are a reflection of permanent atrophy and are often motive of concern for patients and physicians . Skin atrophy is mostly an effect of long‐term use of TCS, but the epidermal and stratum corneum atrophy can be induced even in short‐term treatments.…”
Section: Safety and Tolerability Of Mpamentioning
confidence: 99%
“…При применении один раз в сутки МПА -эффективное и безопасное средство для лечения АД у детей [21,22].…”
Section: клиническая дерматология и венерология 1 2016unclassified
“…18 In a separate study by Chang and colleagues, 25 adherence, and minimal adverse effects, which defines the ultimate goal of chronotherapy in dermatology. 30 Implementation of chronotherapy in AD is a novel and potentially transformative treatment approach. TEWL, hydration, and sebum production have daily variation patterns and should be considered when using topically applied medications to alter absorption of topically applied compounds.…”
mentioning
confidence: 99%